THE CHALLENGES IN TEACHING WRITING BY USING E-LEARNING AT MAN 1 TANJUNG JABUNG TIMUR - Rumaya, Siti (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
The purpose of this study is to determine the difficulties that the teachers at MAN 1 Tanjung Jabung Barat face when attempting to teach writing utilizing online learning. Case study methodology was applied throughout the course of this investigation. The researcher gathered data for this study by conducting interviews, conducting observations, and documenting the findings. The data was evaluated by first simplifying it, then displaying it, and finally drawing conclusions from it. Based on the findings of the data collection, the researcher determined that adopting E-learning to teach writing presents various obstacles for teachers. The use of the e-learning system is based on the subject teacher's position that implementation e-learning is less effective in learning to write, which is one of the obstacles. Other obstacles include students' lack of motivation to understand learning to write, differences in the level of understanding among students in the same class, and a lack of support from parents.